N-Butanol Extract of Gastrodia elata Suppresses Inflammatory Responses in Lipopolysaccharide-Stimulated Macrophages and Complete Freund's Adjuvant- (CFA-) Induced Arthritis Rats via Inhibition of MAPK Signaling Pathway. (22nd January 2020) - He, Peng; Hu, Yiwen; Huang, Changzhao; Wang, Xi; Zhang, Heng; Zhang, Xianping; Dai, Houjie; Wang, Ruiying; Gao, Yan
Abstract : Gastrodia elata is a traditional herbal medicine that has been used for centuries to treat rheumatism. Previous studies have confirmed that ethanol extracts of Gastrodia elata have anti-inflammatory and antioxidant activities, and the n -butanol fraction exerts a higher inhibitory effect. However, the in vivo anti-inflammatory effects of Gastrodia elata have not been evaluated. Thus, we assessed the therapeutic effect of the n -butanol extract of Gastrodia elata (BGE) on complete Freund's adjuvant- (CFA-) induced arthritis rats which were separated into six groups (NOR; MODEL; CFA + dexamethasone (DEX); CFA + 25, 50, 100 mg/kg BGE). The paw swelling, joint radiology, and histology were used to analyze the effect of BGE on delaying the progression of rheumatoid arthritis. Furthermore, serum levels of inflammatory cytokines were analyzed via ELISA. In addition, the effect of BGE on nitric oxide (NO) production, expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2(COX-2), and inflammatory cytokines were detected in lipopolysaccharide- (LPS-) stimulated RAW264.7 macrophage cells. Lastly, the impacts of BGE on the activation of the mitogen-activated protein kinases (MAPK) pathway in CFA rats and LPS-stimulated RAW264.7 macrophage were examined by western blot analysis. The results show that BGE can significantly reduce paw swelling without losing the body weight of rats. Imaging assessment confirms that BGE can protect cartilage from destruction, as well as reducing inflammatory cell infiltration and synovial proliferation. Moreover, BGE suppresses the production of inflammatory cytokines in serum and inhibits the activation of the phosphorylation of p38 and ERK in CFA rats. BGE was also demonstrated to decrease the production of NO and inflammatory cytokines in LPS-stimulated RAW264.7 cells. The effect of BGE in LPS-induced expression leads to reduced p38 and ERK phosphorylation and also downregulates the protein expression of iNOS and COX-2. Taken together, BGE exhibits a potential therapeutic effect on CFA rats, and its anti-inflammatory and antioxidant effects were possibly exerted by regulation of ERK/p38MAPK.